A nonlinear and non-ideal wind generator supporting structure - Brasil, R. M L R F; Feitosa, L. C S; Balthazar, José Manoel [UNESP] (Trans Tech Publications, 2006)
We present a simple mathematical model of a wind turbine supporting tower. Here, the wind excitation is considered to be a non-ideal power source. In such a consideration, there is interaction between the energy supply and the motion of the supporting structure. If power is not enough, the rotation of the generator may get stuck at a resonance frequency of the structure. This is a manifestation of the so-called Sommerfeld Effect. In this model, at first, only two degrees of freedom are considered, the horizontal motion of the upper tip of the tower, in the transverse direction to the wind, and the generator rotation. Next, we add another degree of freedom, the motion of a free rolling mass inside a chamber. Its impact with the walls of the chamber provides control of both the amplitude of the tower vibration and the width of the band of frequencies in which the Sommerfeld effect occur. Some numerical simulations are performed using the equations of motion of the models obtained via a Lagrangian approach.
Keywords: Impact damper; Non-ideal power sources; Non-linear dynamics; Wind turbines; Generator rotation; Impact dampers; Computer simulation; Dynamics; Equations of motion; Lagrange multipliers; Mathematical models; Natural frequencies; Nonlinear systems; Vibration control